KOPERASI SYARIAH BERPERAN SEBAGAI SOLUSI PENINGKATAN PENDAPATAN PARA PEDAGANG PASAR RAKYAT DIKAITKAN DENGAN PERMENDAG NOMOR 21 TAHUN 2021 TENTANG PEDOMAN PEMBANGUNAN DAN PENGELOLAAN SARANA PERDAGANGAN - ISMAK SUBARDAN; MIRZA AMELIA; ISMI ARIFIANA RAHMANDARI (GANEC SWARA, 2023)
The purpose of this study is to explain the role of sharia cooperatives as a solution to increasing the income of people's market traders in relation to Permendag number 21 of 2021, and to explain the existence of sharia cooperatives in facilitating increasing the income of people's market traders in traditional markets. This research method can be qualified as empirical legal research, namely by examining how existing laws are and examining their implementation in the field by looking at the facts that occur in society. The results show that sharia cooperatives continue to strive to provide the best, solutive service to their members, and put forward an attitude of trust so that every program implemented plays a role in helping to increase the income of people's market traders where there is no mindset that they feel chased by interest payments. The existence of sharia cooperatives can unravel the difficulties of people's market traders in anticipating the occurrence of purchasing power for the fulfillment of merchandise where the cooperative always monitors the performance of its consumers. groceries and other types of merchandise